Prototype Development of IoT-Based Real-Time Smart Parking Monitoring System at Polije’s Second Campus in Bondowoso - Ariyadi, David Juli; Hakim, Lukman; Mulyadi, Ely; Hermansyah, Mas'ud; Pradana, Reza Putra (P3M Politeknik Negeri Jember, 2026)
The increasing number of activities and students at Campus 2 of the State Polytechnic of Jember has led to high vehicle usage, creating pressure on limited parking facilities. Current policies relying on manual verification of Vehicle Registration Certificates (STNK) still result in inefficiencies and security risks due to the lack of automated data recording. This research aims to develop an Internet of Things (IoT)-based Smart Parking System with real-time monitoring to address these challenges. The proposed system integrates RFID for rapid identification, while data is recorded in a real-time database (MySQL with API integration) and displayed through a web-based dashboard. A QR code-based STNK scanning mechanism is also incorporated to strengthen vehicle authentication. Based on the results of trials and implementation, the system is able to run optimally with the RFID sensor reading success rate reaching 100% at a distance of 1–2 cm. The database integration performance shows stable results, with the average data storage time in the database being approximately 3.86 seconds, which is still categorized as real-time. This prototype successfully improves data collection accuracy, enables real-time supervision, and provides statistical insights into parking utilization. In conclusion, the implementation of this IoT-based smart parking system is proven to reduce manual intervention, enhance operational efficiency, and support campus parking management that is more transparent, efficient, and measurable. This innovation contributes to the transition toward a smart campus and supports digital governance at Polije’s Second Campus in Bondowoso.